Fathering and Early Childhood Adjustment in Polygamous Families: A Case Study Analysis - Maulida Haura, Farah; Formen, Ali; Sunarso, Ali (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Polygamous family structures present unique challenges to early childhood development, particularly in terms of emotional security, social adaptability, and access to paternal care, yet remain underexplored in academic research. This study explores the role of fathering in shaping early childhood adjustment within polygamous family structures. It investigates how different levels of paternal involvement, such as caregiving, emotional support, and educational engagement, affect children's social and emotional development. Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving two fathers who live separately from one or more of their wives and serve as the sole economic providers in their households. Thematic analysis was conducted to identify patterns of fathering practices and their relation to children's adjustment outcomes. Findings reveal stark contrasts between the two parenting approaches. One father demonstrated high engagement, shared household responsibilities, and fostered autonomy in educational decision-making, contributing to the child’s emotional security and social adaptability. In contrast, the other father adhered to traditional and authoritative roles, fully delegating caregiving to his wives and limiting his children’s external social exposure, which may hinder their emotional development and peer interaction. This study highlights the importance of culturally contextualized fathering and calls for inclusive parenting programs that accommodate diverse family structures, especially within polygamous contexts. However, the study is limited by its small sample size and context-specific focus, which may constrain the broader applicability of its conclusions. Future research is recommended to involve more diverse participants across regions and apply longitudinal methods to explore long-term patterns of fathering and early childhood development within varied family configurations.